Extractibilityof Residual Rock and Superphosphate on Limed and Unlimed Bungor Soil. - Aminuddin, H.; Van der Deelen, J.; Baert, L. (1987)
The possibility of using soil extractants to monitor the transformation of phosphorus (P) fertilizer on a Bungor series soil was investigated. Three soil extractants - Bray 2, Ammonium acetate lactate (AAL) and Olsen - were evaluated. The soil was treated with three levels of P each from rock phosphate and superphosphate at 0, 150 and 300kg Plha, no lime and limed at 4 tons/ha and a P fertilizer application interval of one year. Bray 2 and AAL were able to detect recent P from aged P applications with a higher amount of P being extracted from the recent. These extracts were able to differentiate between the 150 and 300kg Plha treatments but were not able to distinguish the forms of P. Olsen extractant on the other hand was able to detect the two P forms and showed P release from rock phosphate with time.